Microsoft Copilot - Minnick, Chris (John Wiley & Sons, Inc., 2025)
Microsoft is enhancing all its most widely used productivity software--including Windows and apps like Word and Excel--with the power of AI. And now you can learn to make the most of this revolutionary new tool with Microsoft Copilot For Dummies!
Includes index. - Print version record
Keywords: Microsoft Windows (Computer file); Microsoft Office; Natural language processing (Computer science); Artificial intelligence; Chatbots; Traitement automatique des langues naturelles; Intelligence artificielle; artificial intelligence